Technologies for bumper yield in cassava - Raju, Saravanan; Ravi, V; George, James (Indian Horticulture, 2019)
Cassava is tolerant to drought, but it is very sensitive to soil water deficit during the first three months after planting. Water deficit stress at any time during the early period significantly reduces the growth of roots and shoots, and impairs subsequent development of the storage roots. Higher yields have been obtained with supplemented irrigation. Several fold increase in cassava root yield is reported by following required planting methods adjusted to soil moisture conditions under rainfed productions. When soil is not well-drained and too wet owing to heavy rains, it is better to plant stakes on top of ridges or mounds to keep the roots above standing water. However, where cassava is planted during dry periods, sprouting of stakes and plant survival are significantly higher, when cassava stakes are planted on the flat, owing to the slightly higher soil moisture content of the top soil. Stakes should be planted at a shallow depth of 5–10 cm, in heavy and wet soils, but slightly deeper in light-textured and dry soils to avoid surface heat and low moisture. Cassava benefits from supplemental irrigation during rainless periods. During periods of drought, yields increased with increasing amounts of surface irrigation. Full irrigation, at 100% of crop water requirements doubled the root yield as compared to yield obtained without irrigation. Drip irrigation makes more efficient use of water by providing small, frequent applications, which saves water while maintaining soil moisture at a level that is highly favourable to crop growth. In India, drip irrigation produced about the same root yield as flood irrigation (around 60 tonnes/ha using 50% less water). When water applied through drip irrigation is equal to that used in flood irrigation, yields continued to increase substantially to 67.3 tonnes/ha.